Patient reported outcome measures (PRO) in colorectal surgery - Kathia E. Nitsch, BS; Srinivas J. Ivatury, MD, MHA, FACS, FASCRS (Surgery Open Science, 2024)
Patient reported outcomes refer to, “Any report of the status of a patient's health condition that comes directly from the patient, without interpretation of the patient's response by a clinician or anyone else” (US Food and Drug Administration, 2009) [1]. These outcomes can include anything that matters to patients including quality of life, pain, number of bowel movements. Patient reported outcome measures refer to tools or instruments that help to measure these outcomes. These measures can be done using validated tools, those that have undergone rigorous testing and psychometric validation, and non-validated tools such as may exist in a practice to rate practice or physician/staff care quality. For this paper, we will discuss the role of patient reported outcomes measures in colon and rectal surgery.